P-198 Nurse-led care for non-complex dying: a collaboration between hospice and acute hospital. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Wills, Carly; Grove, Sarah
Abstract : The acute trust has severe bed capacity issues. Patients were dying on busy, acute hospital wards but often did not meet the criteria for admission to a specialist hospice bed due to lack of specialist palliative care needs. We had a new purpose-built hospice with extra non-commissioned beds that we knew could benefit our community. Our intention was to allow people to have a dignified death in more suitable surroundings. This resulted in us launching the nurse-led bed initiative; skilled nurses who are trained in caring for people at end of life run the beds with minimal medical input. The service in its first year has seen over 250 patients, saving the acute trust over 2600 bed days. The average length of stay for patients is 10 days. The shortest stay was one hour; the longest 87 days. The feedback from patients and families shows it has been an overwhelming success. Nurses feel empowered to make decisions regarding patient care and have been working in partnership with teams at Cambridge University Hospital to champion the pilot and communicate its success. Patients are feeling more in control by having an alternative to staying in hospital. Families are not limited by visiting hours or other restrictions and can stay overnight. All rooms have access to outside and pets can visit. The next step is to make it a seven day a week service as, due to current resources, it runs Monday to Friday. This may increase occupancy in the beds, thus meaning that an even greater number of patients are likely to have a better experience at the end of life. ' It's just everything it should be; peaceful, light, airy, clean and staff that are attentive and know what's going on. I press the buzzer and they are there .' Patient's relative.